1985
DOI: 10.1104/pp.77.2.309
|View full text |Cite
|
Sign up to set email alerts
|

Osmoregulation in Cotton in Response to Water Stress

Abstract: ABSTRACrCotton (Gossypium hirsutum) (L.) was grown in a sand and nutrient solution system at two levels of phosphorus (0.5 and 5.0 millimolar). Within each phosphorus treatment, plants were either watered daily or acclimated to water stress by subjection to several water stress cycles.Stress acclimation increased leaf starch at the low phosphorus level, but not at the high phosphorus level. High phosphorus increased leaf sucrose and glucose concentration in both acclimated and nonacclimated plants, but had lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0
3

Year Published

1986
1986
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(38 citation statements)
references
References 4 publications
1
34
0
3
Order By: Relevance
“…For instance, enhanced P fungi can dramatically increase a host plant's nutrition can increase stomatal conductance and absorption of mineral nutrients from the soil, transpiration (Radin, 1984;Ackerson 1985; particularly immobile nutrients such as phosphate Auge, 1992), and several investigators concluded (Marschner & Dell, 1994). Safir, Boyer & Gerdemann that increases in stomatal conductance and transpir- (1971) were the first to report that mycorrhizal ation of plants infected by mycorrhizal fungi were infection also alters plant water relations.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, enhanced P fungi can dramatically increase a host plant's nutrition can increase stomatal conductance and absorption of mineral nutrients from the soil, transpiration (Radin, 1984;Ackerson 1985; particularly immobile nutrients such as phosphate Auge, 1992), and several investigators concluded (Marschner & Dell, 1994). Safir, Boyer & Gerdemann that increases in stomatal conductance and transpir- (1971) were the first to report that mycorrhizal ation of plants infected by mycorrhizal fungi were infection also alters plant water relations.…”
Section: Introductionmentioning
confidence: 99%
“…The level of cotton leaf starch required to continue nocturnal carbon export at daytime rates is less than that normally found in nonstressed field-grown cotton (20) but water stress decreases starch levels in cotton leaves (4,20) provided other stress factors do not interfere (1,2). Severe water stress depresses the starch content of cotton leaves (4) to such an extent that carbon export from them should be largely limited to daylight hours.…”
Section: Discussionmentioning
confidence: 97%
“…Increased P supply appears to have an inconsistent effect on the stomatal conductance and growth in various plant species. For example, Atkinson & Davison (1972), Ackerson (1985) and Dosskey et al (1993), reported that increased P supply decreased stomatal conductance in Douglas fir seedlings (Pseudotsuga menziesii), cotton plants (Gossypium hirsutum) and Arctium minus, respectively, whereas transpiration rates increased in tea (Camellia sinesis) and cotton plants (Nagarajah & Ratnasuriya, 1978 ;Radin, 1984). Auge!…”
Section: mentioning
confidence: 99%
“…Although a lower rate of CO # assimilation and growth can generally be attributed to decreased stomatal conductance, Ackerson (1985), Dosskey et al (1993) and Auge! et al (1994) could demonstrate no differences in the growth of their respective plants between low and high P treatments.…”
Section: mentioning
confidence: 99%